Flume testing of passively adaptive composite tidal turbine blades under combined wave and current loading. (February 2020) - Porter, Kate E.; Ordonez-Sanchez, Stephanie E.; Murray, Robynne E.; Allmark, Matthew; Johnstone, Cameron M.; O'Doherty, Tim; Mason-Jones, Allan; Doman, Darrel A.; Pegg, Michael J.
Abstract: The tidal energy industry is progressing rapidly, but there are still barriers to overcome to realise the commercial potential of this sector. Large magnitude and highly variable loads caused by waves acting on the turbine are of particular concern. Composite blades with in-built bend-twist elastic response may reduce these peak loads, by passively feathering with increasing thrust. This could decrease capital costs by lowering the design loads, and improve robustness through the mitigation of pitch mechanisms. In this study, the previous research is extended to examine the performance of bend-twist blades in combined wave–current flow, which will frequently be encountered in the field. A scaled 3 bladed turbine was tested in the flume at IFREMER with bend-twist composite blades and equivalent rigid blades, sequentially under current and co-directional wave–current cases. In agreement with previous research, when the turbine was operating in current alone at higher tip speed ratios the bend-twist blades reduced the mean thrust and power compared to the rigid blades. Under the specific wave–current condition tested the average loads were similar on both blade sets. Nevertheless, the bend-twist blades substantially reduced the magnitudes of the average thrust and torque fluctuations per wave cycle, by up to 10% and 14% respectively. Highlights: Laboratory tests demonstrated the bend-twist response of composite blades. Bend-twist response increases with tip speed ratio. Average loads on the rotor are similar in current and wave–current conditions. Composite bend-twist blades damp the wave induced fluctuations in thrust and torque.